Frutescone O from Baeckea frutescens Blocked TLR4-Mediated Myd88/NF-κB and MAPK Signaling Pathways in LPS Induced RAW264.7 Macrophages - Lin, Xiaobing; Zhang, Junhan; Fan, Decai; Hou, Jiqin; Wang, Hao; Zhu, Lin; Tian, Ruina; An, Xiaofei; Yan, Ming (Frontiers in Pharmacology, 2021)
Frutescone O was isolated from the aerial parts of Baeckea frutescens L., which was commonly used as a folk medicinal material for treating anti-inflammatory disease in South East Asia. This study was aimed to investigate the anti-inflammatory activity and related signaling cascade of Frutescone O (Fru) in LPS induced RAW264.7 cells. The anti-inflammation activity of Frutescone O was determined according to the inhibitory effects on the secretion of nitric oxide (NO), expression of inducible NO synthase, and pro-inflammatory cytokines. The regulation of Myeloid differentiation factor 88 (MyD88), inhibition of NF-κB, and MAPK pathways were further investigated for molecular mechanisms. Fru significantly decreased the expression of iNOS and the production of NO in LPS-stimulated RAW264.7 cells. It also dose-dependently suppressed LPS induced expression of IL-1β, IL-6, and TNF-α. Furthermore, Fru remarkably inhibited the upregulation of NF-κB (p50) expression in the nucleus and the phosphorylation ratio of p38, JNK, ERK, and Myd88 signaling protein. The molecular docking results indicated Fru participated in a powerful and stable interaction with the active site of TLR4-MD2. Thus, Fru suppressed the LPS induced inflammation in RAW264.7 cells by blocking the TLR4 mediated signal transduction through the NF-κB and MAPK signaling pathways, as well as inhibiting the Myd88 and iNOS expression.